Time-of-day effects on muscle mitochondria following short-term ablation of satellite cells - Kahn, Ryan E.; Dinnunhan, Fawzan; Meza, Guadalupe; Lieber, Richard L.; Lacham-Kaplan, Orly; Hawley, John A.; Dayanidhi, Sudarshan (Frontiers in Physiology, 2025)
IntroductionEndurance exercise capacity fluctuates by time-of-day due, in part, to molecular clock effects on muscle physiology. As endurance-based exercise relies predominantly on mitochondria for the conversion of cellular energy, fluctuations observed in endurance capacity have been attributed to diurnal variation in mitochondrial respiration and molecular clock KO animals exhibiting blunted mitochondrial function/content. Recently, a circadian profiling of satellite cells (SCs) demonstrated molecular clock, metabolic, and mitochondrial genes exhibit robust oscillation over 24 h while long-term SC ablation impairs endurance exercise capacity. These lines of evidence suggest SC molecular clocks may influence mitochondrial respiration according to time-of-day. We determined whether mitochondrial respiration differs by time-of-day in the presence and absence of SCs in oxidative (soleus, SOL) and glycolytic (tibialis anterior, TA) muscle.MethodsUtilizing a Pax7CRE−ERT2/+; Rosa26DTA/+ mouse model capable of SC ablation (SC+, SC−), we conducted experiments in either the morning, afternoon, or evening.ResultsIn both SOL and TA, respiratory coupling ratio (RCR) was lowest and Leak-state respiration (TA) was highest in the morning with no differences observed following SC ablation. Utilizing a submaximal ex vivo fatigue protocol that relies predominantly on mitochondrial energy, we observed that submaximal fatiguability was lower in the morning than afternoon in glycolytic muscle (EDL) (morning-SC+: 54 ± 5; afternoon-SC+: 36 ± 6 contractions until fatigue, p < 0.05), which corresponded with peak/trough Bmal1 and CLOCK gene expression in muscle.DiscussionCollectively, the results from the current study suggest that SCs influence mitochondria in a time-of-day manner.